2021
DOI: 10.1002/adma.202004098
|View full text |Cite
|
Sign up to set email alerts
|

Combination of Highly Efficient Electrocatalytic Water Oxidation with Selective Oxygenation of Organic Substrates using Manganese Borophosphates

Abstract: One of the key catalytic reactions for life on earth, the oxidation of water to molecular oxygen, occurs in the oxygen‐evolving complex of the photosystem II (PSII) mediated by a manganese‐containing cluster. Considerable efforts in this research area embrace the development of efficient artificial manganese‐based catalysts for the oxygen evolution reaction (OER). Using artificial OER catalysts for selective oxygenation of organic substrates to produce value‐added chemicals is a worthwhile objective. However, … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
88
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

6
3

Authors

Journals

citations
Cited by 62 publications
(91 citation statements)
references
References 77 publications
(45 reference statements)
2
88
0
Order By: Relevance
“…It completely vanishes in the postreaction mixture (Figure 7b, blue), suggesting full conversion of the starting HMF. [ 50,51 ] The appearance of a peak at ≈7 ppm indicates its conversion to FDCA (Figure 7b, red). It is stimulating to note that with a current density as high as 25 mA cm −2 , full conversion of HMF with a Faradaic yield of 80% can be achieved.…”
Section: Resultsmentioning
confidence: 99%
“…It completely vanishes in the postreaction mixture (Figure 7b, blue), suggesting full conversion of the starting HMF. [ 50,51 ] The appearance of a peak at ≈7 ppm indicates its conversion to FDCA (Figure 7b, red). It is stimulating to note that with a current density as high as 25 mA cm −2 , full conversion of HMF with a Faradaic yield of 80% can be achieved.…”
Section: Resultsmentioning
confidence: 99%
“…[16] Additionally, these well-developed 1D channels in the borophosphate structure could act as the diffusion path for the ions (e.g., OH− or H+) and water molecules enabling further utilization of the active sites located under the surface of the electrocatalyst. [8,17] LiNiFe-borophosphate (LNFBPO) was synthesized by a facile hydrothermal method. For the comparison purpose, LiNi-borophosphate (LNBPO) was also prepared.…”
Section: Materials Structure Analysismentioning
confidence: 99%
“…Considering the observation that, during the OER, most of the usually highly corrosion resistant intermetallic materials transform at least partly to MO x H y phases (M = Fe, Co, Ni), a central research question is to uncover the nature of the newly formed MO x H y phase as it is most likely responsible for the catalytic activity. [ 32,33 ] Recently, it has been shown that the structure of the precursor (e.g., FeSi) and the transformation conditions (e.g., pH or potential) strongly influence the catalytic and chemical properties of the in situ formed catalytically active MO x H y phases. [ 32 ] These considerations explain why MO x H y phases are often more active when they are formed in situ from precursors which contain anions that tend to get oxidized and leach during OER conditions.…”
Section: Introductionmentioning
confidence: 99%